2016
DOI: 10.1128/jvi.00219-16
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Bovine Herpesvirus 1 VP8 Plays a Role in Viral DNA Encapsidation and Is Essential for Its Cytoplasmic Localization and Optimal Virion Incorporation

Abstract: VP8 is a major tegument protein of bovine herpesvirus 1 (BoHV-1) and is essential for viral replication in cattle. The protein undergoes phosphorylation after transcription through cellular casein kinase 2 (CK2) and a viral kinase, US3. In this study, a virus containing a mutated VP8 protein that is not phosphorylated by CK2 and US3 (BoHV-1-YmVP8) was constructed by homologous recombination in mammalian cells. When BoHV-1-YmVP8-infected cells were observed by transmission electron microscopy, blocking phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…As a result, it is less likely to be involved in viral particle transport through the TGN. We have previously shown that inhibiting VP8 from entering the cytoplasm significantly reduced the amount of virion-incorporated VP8 (12). This is consistent with VP8 being localized in the cis-Golgi, which is an important site for protein incorporation into virions.…”
Section: Fig 4 Legend (Continued)supporting
confidence: 80%
See 4 more Smart Citations
“…As a result, it is less likely to be involved in viral particle transport through the TGN. We have previously shown that inhibiting VP8 from entering the cytoplasm significantly reduced the amount of virion-incorporated VP8 (12). This is consistent with VP8 being localized in the cis-Golgi, which is an important site for protein incorporation into virions.…”
Section: Fig 4 Legend (Continued)supporting
confidence: 80%
“…This function seems to be exclusive to US3. It does not appear to need an intermediate kinase to phosphorylate VP8, because US3 and CK2 are the only kinases that phosphorylate VP8 in BoHV-1infected cells (12) and CK2 does not affect the nuclear localization of VP8.…”
Section: Fig 4 Legend (Continued)mentioning
confidence: 99%
See 3 more Smart Citations